Human papillomavirus type 16 E7 associates with a histone H1 kinase and with p107 through sequences necessary for transformation. - Davies, R (1993)
The transforming function of human papillomavirus type 16 (HPV16) E7 has been shown to depend on activities additional to the ability to bind RB. In this paper we describe two further properties of E7 which may also contribute to transformation, an association with a histone H1 kinase at the G2/M phase of the cell cycle and an ability to bind the RB-related protein p107. The region of E7 identified previously as important for RB binding was found to be involved in the association with the kinase and complex formation with p107, although analysis of E7 point mutants within this region revealed a difference in the precise sequence requirement for RB and p107 binding. Association with the kinase activity correlated with the ability to bind RB, but the restriction of the kinase association to the G2/M phase of the cell cycle implies that this activity might not be directly mediated by RB binding. Since kinase-binding-deficient E7 mutants are also transformation defective, this may represent an independent function of E7 which plays a role in the G2/M phase of the cell cycle.